2022
DOI: 10.1029/2022gl099647
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening Dry Spells Intensify Summer Heatwaves

Abstract: A lengthening of dry spells (DSLs) has been reported by some regional studies, but its linkage with heatwaves via the feedback between soil moisture and air temperature is still not clear on the global and continental scales. Here we examine increases in the length of DSLs during summer over the global continents using in situ precipitation records. Globally, the average DSL has increased by 0.46 day/decade since the 1970s along with increased high‐pressure anomalies which are found to be an important reason f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…It is worth mentioning that the heatwaves odds experienced insignificant (P value > 0.05) changes for 23% of stations, including Abadan, Arak, Birjand, Urmia, Zahedan, and Zanjan. Other studies confirmed similar positive tendencies in heatwaves characteristics, summer temperature, and maximum dry spell temperature in different regions around the world (Basha et al, 2017;Deng et al, 2018;He et al, 2022;Jamali et al, 2022;Jyoteeshkumar Reddy et al, 2021;Motamedi et al, 2023;Sato & Nakamura, 2019;Trancoso et al, 2020).…”
Section: Heatwave Duration and Heating Ratesupporting
confidence: 65%
“…It is worth mentioning that the heatwaves odds experienced insignificant (P value > 0.05) changes for 23% of stations, including Abadan, Arak, Birjand, Urmia, Zahedan, and Zanjan. Other studies confirmed similar positive tendencies in heatwaves characteristics, summer temperature, and maximum dry spell temperature in different regions around the world (Basha et al, 2017;Deng et al, 2018;He et al, 2022;Jamali et al, 2022;Jyoteeshkumar Reddy et al, 2021;Motamedi et al, 2023;Sato & Nakamura, 2019;Trancoso et al, 2020).…”
Section: Heatwave Duration and Heating Ratesupporting
confidence: 65%
“…Because ET plays a vital role in modulating surface air temperature through cooling effects. The reduction in ET may increase sensible heat flux, thereby increasing the air temperature and even leading to heat waves (He et al, 2022). In the case of this study, the potential decrease in ET during September and October may be associated with reinforced stomatal closure, simultaneously leading to a decline in photosynthesis, which can be corroborated by the findings of the extremely low levels of vegetation productivity in the same period (Zhao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in Bangladesh, rainfall is dropping by 75% during the monsoon season (Monir et al 2023a). Since the 1970s, the worldwide mean dry spell length (DSL) has grown by 0.46 days each decade (He et al 2022). Droughts are natural climatic catastrophes that occur in speci c parts of the world during dry spells with minimal precipitation caused by a lot of ocean and local factors (Breinl et al, 2020;Faiz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the present study, 82.35% of weather stations are rising for short dry spells, 73.53% in medium-length dry spells, and 50% in long dry spells. Also, since the 1970s, the worldwide mean dry spell length (DSL) has grown by 0.46 days each decade(He et al 2022). Dry season spells across South America and southern Africa are getting longer, up to about two days every decade, while those over West Africa are getting shorter, around the same length).…”
mentioning
confidence: 99%